Developing HOTS questions for the materials of human and animals respiratory organs for Grade V of elementary school - Aulia Latifah; Ika Maryani (Jurnal Prima Edukasia, 2021)
The study aims (1) to know the resulting development HOTS questions for the materials of human and animal respiratory organs for grade V of elementary school, and (2) to test the quality of questions for the materials of human and animal respiratory organs for grade V of elementary school. This study is a Research and Development (RD) with ADDIE methods (analysis, design, development, implementation, and evaluation). The research subjects were 90 grade V elementary school students. Observation data through interviews, documentation, questionnaires, and tests. The data analysis technique uses qualitative data from Miles and Huberman’s models, while quantitative data uses descriptive and inferential statistical data to calculate the result of the expert test (material and evaluation experts) and empirical test (validity, reliability, Difficulty index, discriminant index, and deception). The study results stated that (1) the validity of the first test that was classified as valid was 13 questions and 32 questions were invalid, while the second test, which was classified as valid, was 44 questions, and 1 question was invalid. The first reliability has sufficient and low criteria, while the second test has high and sufficient criteria. The Difficulty index of the first and second test items has difficult, medium, and easy criteria. The discriminant index of the first test has the criteria of being insufficient, sufficient, good, and some questions do not have a discriminant index, while the second test has the criteria for being insufficient, sufficient, and good. The effectiveness of the first test distractor had 48,89% functional distractor and 51,11% non-functioning, while the second test had 75,55% functional distractor and 24,44% non-functioning, and (2) quality of question development HOTS from the results of material expert validation and evaluation obtained a value of 84,52% with very feasible criteria. Based on these assessment results, the question development is HOTS is feasible to be applied in school.